Plasma cystatin C and estimates of glomerular filtration rate using cystatin C independently diagnosed acute kidney injury in critically ill patients with sepsis - Md Ralib, Azrina; Ab. Rashid, Iqbalmunauwir; Nanyan, Suhaila; Ramly, Nur Fariza; Mat Nor, Mohd Basri (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2017)
Introduction: Plasma Cystatin C (CysC) is as an early functional marker for acute kidney injury. Estimates of glomerular filtration rate using CysC (eGFRCysC) has been used in some clinical setting. We evaluated the utility of CysC and eGFRCysC in diagnosing AKI and predicting death in critically ill patients with sepsis. Methods: This is an interim analysis of single centre, prospective observational study of critically ill patients. Inclusion criteria were patients older than 18 years old with sepsis and procalcitonin > 0.5ng/ml. Plasma creatinine and CysC were measured on admission, and eGFRCysC was calculated. AKI was defined based on the plasma creatinine criteria of the KDIGO guideline. Results: Thirty one patients were recruited so far, of which 13 (41.9%) had AKI and six died. CysC were higher in patients with AKI versus No AKI (p<0.001), and correspondingly, eGFRCysC were lower (p=0.006). CysC and eGFRCysC on ICU admission diagnosed AKI with an AUC of 0.88 (0.72 to 1.00), and 0.79 (0.62 to 0.96), respectively. Both did not predict death (AUC 0.59 (0.31 to 0.87) and 0.59 (0.31 to 0.86), respectively). After adjusting for age and SOFA score, both CysC and eGFRCysC independently diagnosed AKI (OR 13 (1.5 to 115) and 1.03 (1.01 to 1.06), respectively). The ideal cut-off point for diagnosing AKI for CysC was 1.5 mg/dl (84% sensitivity and 89% specificity) and for eGFRCysC 77 ml/min (72% sensitivity and 84% specificity) Conclusions: Plasma CysC and its estimated GFR independently diagnosed AKI in critically ill patients with sepsis. We suggest an ideal cut-off points of 1.5 mg/dl and 77 ml/min that can be used in the clinical setting in this cohort of patients.